Corporate governance, critical junctures and ethnic politics: Ownership and boards in Malaysia. (September 2018) - Mohamad-Yusof, Nor Zalina; Wickramasinghe, Danture; Zaman, Mahbub
Abstract: Quotas and affirmative policies are often implicated in debates on corporate governance. This paper examines critical junctures and the role of willful actors in mobilizing their ethnic and political positions to affect governance reforms in Malaysia since independence. We trace the trajectory of Bumiputera affirmative policy in shaping equity ownership and composition of boards of directors using historical institutionalism as a lens. We find ethnic politics has been an endogenous force resulting in Malay share of equity ownership rising from negligible levels to over 20 percent and almost half of the boards of directors of listed companies comprising of Malays. Our analysis shows that governance is a representation, as well as a manifestation, of how ownership and board structures are institutionally reproduced rather than a mere response to global isomorphic pressures.